Sedimentological, geochemical and paleontological insights applied to continental omission surfaces: A new approach for reconstructing an eocene foreland basin in NW Argentina - del Papa, Cecilia Eugenia (2010)
An Eocene foreland basin linked to the Andean uplift in northwestern Argentina has recently been proposed. The basin is divided and partially eroded due to subsequent Neogene orogenic phases, so that a simple reconstruction is insufficient to describe complex field relationships. This presents a new challenge in understanding the initial phases of Central Andean evolution. We propose a multidisciplinary approach in key locations and/or at key geological features as a way to reconstruct the Paleogene basin. In this contribution, we report on sedimentological and geochemical evidence of a conspicuous weathering surface in the continental Eocene Lumbrera Formation and provide an age estimate based on vertebrate mammalian biostratigraphy and an absolute U/Pb zircon age of 39.9 Ma. Weathering surfaces become evident when diagnostic features like paleosols, karsts, and trace fossils are distinctive but, in our case, these characteristics only emerge through detailed sedimentological and geochemical surveys. The Lumbrera paleosurface is represented by a hardened level (20-30 cm thick) characterized by moderately developed reddish paleosols. Moreover, major and trace element profiles show inflections at the top and/or base of the weathered horizon delineating it. A modified form of the chemical index of alteration shows that chemical leaching was moderate and not extensive. In addition, mammalian fossil records substantially differ below and above the weathered paleosol-bearing surface. We conclude that this horizon represents a Middle Eocene omission surface and represents a key level marking a major basin change in northwest Argentina, adding a new constraints for Eocene foreland reconstruction. © 2009 Elsevier Ltd. All rights reserved.